2005
DOI: 10.1063/1.2140080
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the structures of nanoparticles in flames by in situ detection of scattered x-ray radiation

Abstract: The angular pattern of scattered synchrotron x-ray radiation has been used to measure the composition of molecules and nanometer-sized particles in flames. The measured patterns were compared with patterns obtained from calculations for different species compositions. After ensuring that the calculations could reproduce the experiments for air and for ethylene flames under two different combustion conditions flames under special particle producing conditions were studied. In one case, the patterns showed a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…We and others have recently used Small Angle X-ray Scattering (SAXS) [14][15][16][17][18][19][20][21][22][23] and Small Angle Neutron Scattering (SANS) [24,25] techniques to study in situ the size and distribution of soot particles in diffusion flames. In an extension of our work, we have investigated the change in the size and number of soot particles that occurs when water is injected into an ethylene flame.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have recently used Small Angle X-ray Scattering (SAXS) [14][15][16][17][18][19][20][21][22][23] and Small Angle Neutron Scattering (SANS) [24,25] techniques to study in situ the size and distribution of soot particles in diffusion flames. In an extension of our work, we have investigated the change in the size and number of soot particles that occurs when water is injected into an ethylene flame.…”
Section: Introductionmentioning
confidence: 99%
“…Since X-ray attenuation is weaker for hydrogen than for carbon (for 10 keV radiation it as about 73 times), hydrogen detection can thus be three orders of magnitude more sensitive utilizing cold neutrons instead of hard X-rays. In practice, neutrons would be able to detect pressurized gaseous hydrogen surrounding carbon nanoparticles and thus be well-suited for the study of the interaction hydrogen and methane with carbon nanoparticle assemblies such as soot, the structure of which can be characterized by X-ray scattering techniques (see [5][6][7]9,11] and references therein).…”
Section: Characterization Of the Soot Materialsmentioning
confidence: 99%
“…Different carbon structures can be produced from combustion-like processes, such as fullerenes, nanotubes, and graphite. These may be found as components [2][3][4][5] in carbon soot, one of the most common unwanted by-products from incomplete combustion, which normally has a negative effect on health and the environment. It can also have positive aspects in that it may play an important role for clean energy conversion in combustion due to its material properties such as low density and fractal structure.…”
Section: Introductionmentioning
confidence: 99%
“…The computer (NI PXI-1042) had a dual core processor enabling programs to be executed in parallel, meaning that data acquisition and processing could be run at the same time on each processor and that data were sampled continuously without processing dead time. The scattered intensity I i at channel i can be described by the following equations, based on previous works: 23,33 …”
Section: Signal Processingmentioning
confidence: 99%
“…[8][9][10][11] One of the most promising tools for particle dynamics studies is based on synchrotron x-ray scattering, [12][13][14] which has demonstrated the ability to study soot formation in flames in situ: small-angle x-ray scattering (SAXS) to characterize the size distribution of soot particles, [15][16][17][18][19][20][21] and wide-angle x-ray scattering (WAXS) to study the subnanometer structure. 22,23 These scattering techniques measure the intensity of scattered photons as a function of the exchanged momentum, q, according to…”
Section: Introductionmentioning
confidence: 99%